358 DIFFERENTIAL GENE EXPRESSION IN B CELLS FROM GULLAH LUPUS PATIENTS AND CONTROLS. (10th December 2015) - Shu, C.; Guo, L.; Bruner, G.; Gilkeson, G.; Kamen, D.; Tang, Y. H.; Dozmorov, I.; Kelly, J.; Ning, J.; Williams, D.; Pongratz, C.; James, J.; et al.
Abstract : Purpose: The Gullah population has a very low level of European admixture and has higher homogeneity in terms of environmental and genetic influences. The incidence of systemic lupus erythematosus (SLE) is high and the clinical manifestations of Gullah SLE patients are also often severe. Therefore, such characteristics may help us identify more easily, through gene expression microarrays, the genes involved in the pathogenesis of SLE. We studied gene expression in Epstein-Barr virus transformed B cell lines derived from Gullah SLE patients and matched unrelated controls to identify candidate genes or pathways important in the development of lupus. Methods: 6 Gullah SLE patients were selected according to American College of Rheumatology (ACR) criteria for SLE. 6 controls were matched by age, sex, race, and state of residence. Human genome U133 plus 2.0 arrays (Affymetrix) were used for each subject. Gene expression differences were evaluated for genes with p < .05 for the paired t -test, p < .0001 for the associative t -test, and an apparent ratio of expression of > 2.0 or < 0.5. Results: Two separate independent tests of these 6 pairs were done. The consistency between these two tests is 62%. Samples from the Gullah lupus patients differently expressed 299 genes when compared to controls (284 up-regulated, 15 downregulated). The differentially expressed genes include small nuclear ribonucleotide proteins, apoptosis pathway members, signal transduction pathway members, and ubiquitin specific protease related genes. Several genes are located in lupus susceptibility loci. Conclusions: Differential gene expression analysis of cell lines derived from Gullah lupus patients and controls has allowed us to identify promising candidate genes and associated pathways that promise to be important to understanding lupus.